Forced frequency locking of rotating waves - Recke, L. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We describe the frequency locking of an asymptotically orbitally stable rotating wave solution of an autonomous S1-equivariant differential equation under the forcing of a rotating wave.